CULTURE OF PEDAGOGICAL INTERACTION IN EDUCATIONAL PROCESS MANAGEMENT - Niedre-Lathere, Kristīne; Samuseviča, Alīda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In the publication the necessity of comprehensive educational establishment teachers’ mutual systemic and structured interaction with the school administration has been raised The need for teachers’ professional proficiency development and collaboration with methodological work doers for an efficient educational process provision are especially emphasized, as well as urgency for new productive cooperation models has been marked out, which, providing pedagogical interaction, gives an opportunity to increase in a qualitative way pupils’ achievements, the study process outcome improvement in the education content during the time of changes or transformation. The authors of the article raise a hypothetical question whether interaction among the subjects involved in intervention actually exist and how efficient it is, in order to move towards common goal implementation and qualitative development of pupils’ outcomes in the discourse of multistage cooperative relationships. Observing and analysing the course of educational establishments’ different pedagogical and management processes, features have been detected that the aspects of interaction culture are uncertain, which reveals challenges for search of a new approach to collaborative models.